(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
In Uzbekistan, the wool processing industry is not yet fully developed, and the semi-coarse fibers of local sheep are considered a difficult raw material due to their roughness, low elasticity, and disproportionate properties. This study analyzes changes in the strength, elasticity, and tensile characteristics of softened wool fibers. Based on regression modeling, technological trends and optimal parameters of seasonal fibers were determined. The results show that the softening of fibers increases production efficiency, and the developed models serve to prepare high-quality yarn and strengthen export potential.